Who is going to walk? A review of the factors influencing walking recovery after spinal cord injury - Scivoletto, Giorgio; Tamburella, Federica; Laurenza, Letizia; Torre, Monica; Molinari, Marco (Frontiers in Human Neuroscience, 2014)
The recovery of walking function is considered of extreme relevance both by patients and physicians. Consequently, in the recent years, recovery of locomotion become a major objective of new pharmacological and rehabilitative interventions. In the last decade, several pharmacological treatment and rehabilitative approaches have been initiated to enhance locomotion capacity of SCI patients. Basic science advances in regeneration of the central nervous system hold promise of further neurological and functional recovery to be studied in clinical trials. Therefore, a precise knowledge of the natural course of walking recovery after SCI and of the factors affecting the prognosis for recovery has become mandatory. In the present work we reviewed the prognostic factors for walking recovery, with particular attention paid to the clinical ones (neurological examination at admission, age, aetiology gender). The prognostic value of some instrumental examinations has also been reviewed. Based on these factors we suggest that a reliable prognosis for walking recovery is possible. Instrumental examinations, in particular evoked potentials could be useful to improve the prognosis.